E-Commerce and Digital Marketing Strategies: Their Impact on Startupreneur Performance Using PLS-SEM - Sutisna, Felix; Lutfiani, Ninda; Anderson, Evelyn; Danang, Danang; Syaidina, Musidiansyah Otto (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
Startup entrepreneurs are increasingly relying on technology to manage their businesses, particularly through the use of E-Commerce platforms and digital marketing strategies. This study investigates the impact of these technologies on the performance of startup entrepreneurs. Conducted through an online survey of 150 Indonesian startup entrepreneurs from various industries, the research used a questionnaire to evaluate the extent of E-Commerce application usage, digital marketing efforts, and entrepreneurial performance, with a focus on revenue growth, customer satisfaction, and market visibility. The results indicate that the use of E-Commerce platforms has a significant and positive impact on startup performance. Entrepreneurs who actively use these platforms experience higher revenue growth and enhanced customer satisfaction. Furthermore, digital marketing strategies were found to positively influence business performance, particularly in terms of improving market visibility and expanding market reach. This research provides valuable insights into how technology and digital marketing can enhance startup performance. The key takeaway is that integrating E-Commerce platforms and digital marketing strategies into startup growth plans is essential. By investing in digital technologies and improving on- line marketing skills, startup entrepreneurs can achieve greater business success.